Meningkatkan Kemampuan Kerja Sama Pada Siswa Menggunakan Model Sinergi Di Kelas V SDN Alalak Selatan 2 Banjarmasin - Nor Aulia Maulidarrahmah; Aslamiah (CV. ITTC INDONESIA, 2024)
Students' inability to work together effectively is the main problem in this research. The SYNERGY learning approach was used to try to fix this problem. Examining student actions, collaboration capacity, and learning outcomes, as well as describing teacher activities are the objectives of this research. This research uses a three-meeting qualitative strategy based on PTK style classroom action research. Fifteen fifth grade students were used as research subjects. Teacher and student actions and their capacity to work together were observed to collect qualitative data. Worksheets, individual and group evaluation forms, and written tests enable the collection of measurable data regarding student learning outcomes. According to the study, teachers met the